Structural design and evolution of a novel Bi3+-doped narrow-band emission blue phosphor with excellent photoluminescence performance for wide color gamut wLED. Issue 41 (11th October 2021) - Piao, Siqi; Wang, Yichao; Zhu, Ge; Zhang, Jinsu; Zhang, Xizhen; Wu, Danyang; Cao, Yongze; Li, Xiangping; Chen, Baojiu
Abstract : A series of novel garnet structure narrow-band blue emission phosphors Ca4 HfGe3− y Si y O12 : x Bi 3+ (0 ≤ x ≤ 0.04, 0 ≤ y ≤ 0.9) with great color purity and enhanced thermal stability have been successfully developed and synthesized. Abstract : Nowadays liquid crystal display (LCD) backlighting has become an independent subject of the display field, and gradually formed an innovative and popular research area. The narrow-band emission phosphors that play an important role in LCD backlighting have been extensively investigated in recent years. Hence, a series of novel garnet structure phosphors Ca4 HfGe3− y Si y O12 (CHGSO): x Bi 3+ (0 ≤ x ≤ 0.04, 0 ≤ y ≤ 0.9) were designed and synthesized via the high temperature solid state reaction. All the samples belong to a cubic crystal system with the space group of Ia 3̄ d . Under the excitation of near-ultraviolet (n-UV) LED chips, Ca4 HfGe3 O12 (CHGO):0.02Bi 3+ exhibits a narrow-band blue emission with a high color purity of ∼95%, a central wavelength of 432 nm and the full-width at half maximum (FWHM) of around 36.4 nm, which is better than commercial blue phosphors (BAM: Eu 2+ ). CHGO:0.02Bi 3+ also presents an excellent quantum efficiency of 88.7%. The thermal stability is enhanced by the substitution of Si 4+ for Ge 4+, and the Ca4 HfGe3− y Si y O12 :0.02Bi 3+ ( y = 0, 0.3, and 0.6) could remain at 51%, 58%, and 70% at 150 °C of the initial intensity at room temperature, respectively, which is related to the variation of the energy band structure. Simultaneously, our samples have the narrowest FWHM and highest color purity in the reported Bi 3+ -doped blue phosphors. Using K2 SiF6 :Mn 4+ as the red phosphor, β-sialon:Eu 2+ as the green phosphor, Ca4 HfGe2.4 Si0.6 O12 :0.02Bi 3+ as the blue component and GaN-based chip, this optimized w-LED device shows a wide color gamut of 77% NTSC. This is comparable to the current commercial portfolio (β-sialon:Eu 2+ + K2 SiF6 :Mn 4+ + blue chip). All of the results indicate that the Bi 3+ -activated CHGSO phosphors have a wide application prospect in the field of advanced backlight display, which provide a reference and support for the design of near-ultraviolet excited backlight materials.